The Effect of Classic Chest Physiotherapy on Postoperative Pain Scores and Hospital Stay in Patients Undergoing Off-Pump Coronary Artery Bypass Graft Surgery: A Randomized Clinical Trial: - Zolfaghari, Mohammad; Mirhosseini, ÙSeyed Jalil; Baghbeheshti, Maryam; Bauer, Brent A. (Galen Medical Journal, 2018)
Background: Chest physiotherapy (CPT) is a care that increases the mobilization of several structures from both muscle and subcutaneous tissue. We planned to investigate the effect of classic CPT on pain, fatigue, satisfaction, and hospital length of stay (LOS) in patients undergoing off-pump coronary artery bypass graft (CABG). Materials and Methods: This study was a randomized controlled trial that conducted on 50 patients undergoing elective off-pump CABG. The patients have been randomly divided into two groups; in the group A (n=25) patients received physiotherapy at a single session of classic CPT, 4 times during 2nd to 5th days for 15 minutes in every session, in the group B (n=25) patients had not protocol of this exercise therapy (control). Results:The average age of all participants was 62.08 ±9.08 years. Of the 50 patients, 33 (66%) was male. Classic CPT significantly decreased pain (P=0.04), hospital LOS (P=0.010) and could increase in patients’ satisfaction (P<0.001). However, it had no considerable effect on fatigue (P=0.725). Conclusion: According to our findings, classic CPT could improve postoperative care after off-pump CABG surgery. [GMJ.2018;7:e838]